Evaluation of Real-Life Investigational Use of Enoximone in Asthma, the Third Step in Drug Repurposing: A Preliminary Report - Jan Beute; Pieter Boermans; Alex KleinJan (Canadian Respiratory Journal)
Background. The population of uncontrolled asthma patients represents a large therapeutic burden. The PDE3-inhibitor enoximone is a strong and quick bronchodilator and is known to successfully treat life-threatening bronchial asthma (status asthmaticus). Translational mice models showed anti-inflammatory effects when PDE3 was targeted. Methods. Here, we investigated the effectiveness of PDE3-inhibitor enoximone as oral treatment for chronic asthma in a real-life off-label setting. Investigational use of PDE3-inhibitor enoximone: 51 outpatients (age 18–77) with chronic asthma were followed using off-label personalized low doses of the PDE3-inhibitor enoximone. Duration of treatment was 2–8 years. Results. Four groups could be distinguished as follows: The first group includes patients who use enoximone as an add-on, because it helps them in maintaining a better general wellbeing; they still use their traditional medication (n = 5). The second group consists of patients who use enoximone and were able to phase down their traditional medication without deterioration of their asthma symptoms (n = 11). The third group comprises patients who were able to discontinue their traditional medication and use only enoximone without deterioration of their asthma symptoms (n = 24). The last one has patients who, after having used enoximone for some time, saw their symptoms disappear and now use no medication at all, not even enoximone (n = 11). All patients reported improvement or at least alleviation of their asthma symptoms. All patients reported a better quality of life and greater drug compliance. Conclusion. The evaluation shows that PDE3-inhibitor enoximone is a viable alternative for or addition to current asthma therapeutics, as both add-on and stand-alone, considerably reducing the use of LABAs/SABAs/ICS, with no or negligible side effects. Additional studies are advisable.